Ответы и объяснения

2014-03-07T10:10:45+00:00
15+6(3и+4)=0
15+18и+24=0
18и=0-24-15
18 и=-39
и=-39:18
и=-2,17
15+6(3*(-2,17)+4)=0
15+6*(-2,51)=0
15-15=0  

4х=7(2х-3)+46
4х=14х-21+46
4х-14х=46-21
-10х=25
Х=25:-10
Х=-2,5
4*-2,5=7(2* (-2,5)-3)+46
-10=7*(-8)+46
-10=-56+10
-10=-10  
3(t-4)-6=5(t-3)
3t-12-6=5t-15
3t-5t=-15+12+6
-2t=3
t=3: (-2)
е=1,5
3((-1,5)-4)-6=5((-1,5)-3)
3*(-5,5)-6=5*(-4,5)
-16,5-6=- 22,5
-22=-22

2-5(2у-1)=3(4-у)+9
2-10у+5=12-3у+9
-10у+3у=12+9-2-5
-7у=14
У=14: (-7)
У=-2
2-5(2*(-2)-1)=3(4-(-2))+9
2+5*5=3*6+9
2+25=18+9
27=27